A Comparative Study of the Initial and Final Setting Times Between Al-Fetaih Libyan Cement and Beni Suef Egyptian Cement - عبد الرازق محمد موسي المهيوب; ايمان عطية الصالحين (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to conduct a laboratory comparison between the initial and final setting times of Libyan Al-Fataih cement and Egyptian Beni Suef cement, with the objective of evaluating the early hardening behavior of Portland cement. The tests were performed using the Vicat apparatus in accordance with ASTM C191 standards, utilizing samples prepared under appropriate laboratory conditions in terms of temperature and water-to-cement ratio. The results revealed clear differences in setting times between the two cement types, where Al-Fataih cement exhibited a longer setting time compared to Beni Suef cement. These findings suggest that variations in chemical composition, gypsum content, and fineness are among the key factors influencing setting time. The study recommends taking these differences into consideration when selecting the appropriate type of cement for various construction conditions, particularly in high-temperature regions where a longer setting time is necessary to ensure proper workability and construction quality.